(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The development of modern technology is the gateway to a completely different world, one where education is governed not by the educator’s ability to teach; or his / her capability to pass on knowledge to learners, but rather by the availability of technological advancements which can be used as educational tools as well as a way in which to access, manipulate and create data and information. In this essay I shall discuss the use of Information and Communication Technology (ICT) in History Education, while paying special attention and focusing a great deal on the use of iPods as a newly emerging and promising medium through which to teach History.